Bacterial Communities in the Endophyte and Rhizosphere of White Radish (Raphanus sativus) in Different Compartments and Growth Conditions - Sun, Nan; Gu, Yizhu; Jiang, Guoxia; Wang, Yuxin; Wang, Pingzhi; Song, Weitang; Ma, Peifang; Duan, Yabin; Jiao, Ziyuan (Frontiers in Microbiology, 2022)
Endophyte resources have important research value in multiresistance breeding, ecological protection, germicide development and other fields. In this study, high-throughput sequencing (Illumina-MiSeq) technology was employed to analyse the diversity and community composition of white radish (Raphanus sativus) endophytes and rhizosphere bacteria in different compartments and cultivation conditions, including greenhouse and open field cultivation, at both the phylum and genus levels. Alpha diversity index analysis showed that the bacterial richness and diversity values of rhizosphere bacteria were higher than those of endophytes in different compartments. NMDS analysis and microbial co-occurrence network analysis showed that apart from the similarity in the endophytic bacterial composition of the leaf and root endosphere, the endophytic bacterial composition in flesh and epidermis of radish were also more similar. The dominant endophytic bacteria in white radish were Proteobacteria, Bacteroidetes and Actinomycetes at the phylum level. We analyzed the effects of different ecological compartments and two cultivation environments on radish microorganisms, and found that ecological compartments played an important role, which was related to the mechanism of microbial assembly in plants. The same facility cultivation can also improve the diversity of radish microorganisms in different ecological compartments, and change the biomarkers that play a major role in rhizosphere microorganisms and endophytes of radish. Bacteria plays an important role in the process of plant growth, and the study of endophytes enriches the understanding of microbial diversity in white radish, which helps to provide insight into the ecological function and interaction mechanisms of plants and microorganisms.